Citizenship as Property, Not So Valuable - Spiro, Peter (Les ateliers de l'éthique / The Ethics Forum, 2012)
With The Birthright Lottery: Citizenship and Global Inequality, Ayelet Shachar is the first major scholar to put the rich theory of property law theory to work in the realm of citizenship. Assessed on its own criteria, the book delivers on its promise to shake up our thinking on this question. Nevertheless, I argue in this paper that her account is not ultimately persuasive. First, Shachar takes for granted that citizenship is a valuable resource. I suggest that today legal residency is more highly valued that citizenship. Also her defense of the state and the social advantages of having stable citizenship regimes does nothing to confront its decline as the central organizing principle of political life. Last but not least, the modalities of a birthright citizenship levy calls into question the underlying analysis. For instance, the current proposal looks undistinguishable from foreign aid and it would demand much more robust institutional organs of global governance that now exist. The second prong of her argument works at the domestic level as it tackles the problem of under- and over-inclusiveness of birthright citizenship. Here too I have reservations highlighted by modes of implementation.